Karen's secret valentine - Martin, Ann M., 1955-; Tang, Susan (New York : Scholastic, 1997)
Karen's class is having a secret Valentine exchange and she picks her enemy Pamela, but she decides to be nice anyway. Pamela starts receiving mean notes that Karen did not write and other mix-ups start happening. Karen and her friends try to discover who has been messing up the Valentine's fun.
"A Little Apple paperback."
2.8
3-6
3-6
Keywords: Schools -- Fiction; Valentine's Day -- Fiction; School stories; Valentine's Day -- Fiction